PENGELOLAAN ARBORETUM WISATA GAMBUT DI KAMPUNG JAWA KECAMATAN BUKIT BATU KABUPATEN BENGKALIS - Oktina, Roma Silvia; ", Musadad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The Peat Tourism Arboretum is the only peat tourism in Bengkalis, the location of the Peat Tourism Arboretum is in Kampung Jawa, Bukit Batu District. This study aims to (1) find out who the stakeholders in the Peat Tourism Arboretum are. (2) to describe the management of the Peat Tourism Arboretum. (3) to find out what are the obstacles in the management of the Peat Tourism Arboretum. This study uses qualitative methods, the data obtained by collecting data in the field. Data collection techniques were carried out by means of in-depth interviews, document studies, and observations. The analysis used in this research is data reduction, data presentation, and conclusion drawing. The results showed that the stakeholders in the Peat Tourism Arboretum were CSR Pertamina RU II Sungai Pakning, Sungai Pakning Urban village and Koperasi Tani Tunas Makmur Cooperative. Meanwhile, tourism management which includes planning, organizing, directing, and supervising shows that everything is going well. Finally, obstacles in tourism management include the COVID-19 pandemic, internal relations, damaged facilities and promotions.Â Kata Kunci: Peat Tourism Arboretum, Management, Stakeholder